Population Health Management in Fragmented Healthcare Systems: Toward a Conceptual Framework Adapted to the Peruvian Context for Intersectoral Coordination and the Reduction of Health Inequities (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
The Peruvian healthcare system exhibits marked institutional fragmentation, which generates inequities in access to services, particularly among vulnerable populations. In this context, the Population Health Management (PHM) model serves as a strategic approach to improving health outcomes through population segmentation, risk stratification, and intersectoral coordination. This study aimed to propose a conceptual framework adapted to the Peruvian healthcare system for the implementation of PHM within contexts of institutional fragmentation. A scoping review of literature published between 2015 and 2025 was conducted using international and regional databases. The results highlight gaps in the management of chronic diseases, limited coordination between subsystems, and persistent inequities in access to healthcare services. Furthermore, a scarcity of scientific production aligned with institutional priorities was identified. It is concluded that implementing the PHM approach in Peru requires strengthening integration across subsystems through strategies involving segmentation, risk stratification, and intersectoral articulation. The proposed framework constitutes a relevant tool for health management and policy formulation.
Keywords: Population health management; health system fragmentation; integrated care; health inequities; intersectoral coordination